Mapping light strand transcripts near the origin of replication of Xenopus laevis mitochondrial DNA. - Bogenhagen, D F (1990)
Transcription of the light strand of Xenopus laevis mitochondrial DNA initiates at two promoters located approximately 350 to 450 nucleotides upstream from the 5' ends of major D-loop DNA strands. Small RNAs within this region have been mapped by blot hybridization, primer extension and S1 nuclease protection methods. The results reveal that the large majority of RNAs within this region have 3' termini located at a sequence element, designated CSB 2, that is conserved in sequence and position in Xenopus, mouse, rat and human mtDNA. However, the X. laevis CSB 2 appears to be a site of RNA processing only, since RNA-to-DNA transitions are not detectable at this site. RNAs containing sequences downstream of CSB 2 are extremely rare. A significant fraction of these RNAs are processed by cleavage at a site just upstream of the most predominant 5' ends of D-loop DNAs. We suggest that RNA processing at this site may play a role in priming mtDNA replication.